Boundary-layer transition on wings in ground effect - Roberts, L. S. (Cranfield University, 2017)
The competitiveness of a high-performance racing car is extremely reliant on aerodynamics. Due to the current economic climate, track testing is often forsaken and the majority of aerodynamic development carried out using sub-scale wind tunnel testing and computational simulations. It is important, therefore, that experimental and computational approaches represent real-world conditions as closely as possible. Although racing cars travel at much higher speeds than typical passenger cars, in comparison to aircrafts they still operate at relatively low Reynolds numbers and, consequently, laminar and transitional phenomena are evident. Despite this, the bulk of relevant literature available for racing-car aerodynamics is undertaken with little regard to the influence of Reynolds number, and in the case of computational studies, the omission of laminar and transitional phenomena all together. The present work has demonstrated, using a super-scale two- dimensional wind-tunnel model, that laminar and transition flow phenomenon are important at Reynolds numbers equivalent to a full-scale racing car. Moreover, the influence of these aspects increased as the wing’s ground clearance reduced; meaning that in ground effect they are even more important. Further experiments with three-dimensional models of varying complexity, from a simple single-element wing to a highly complex F1-specification wing, showed that laminar phenomena are important for F1 applications as well as for lower-downforce capability racing cars. A transition-sensitive eddy-viscosity turbulence model, k-kL-w, was used to simulate inverted wings operating in ground effect. It was shown that that laminar and transitional flow states could be simulated easily inside a commercial solver, and that the model offered a substantial improvement over the classical fully-turbulent k-w SST in terms of both force coefficient prediction and surface-flow structures. This experiments and computational simulations described in this thesis show the Reynolds number sensitivity of, and importance of laminar phenomenon on, wings operating in ground effect. It has been shown that laminar boundary layers are an important aspect of the flow characteristics of wings in ground effect, at both full-scale and model-scale Reynolds numbers. As such, it is recommended that future studies incorporate laminar and transitional phenomena.